Budżety projektów - Łada, Monika (The Budgets of the Projects, 2006)
In Polish management accounting literature the growing interest on applications in project environment are currently observed. The focus of this paper is on the concept of project budgeting. In particular such issues as budgeting functions in project management process, project data presentation in budgets and classifications of project budgets are discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 242-251